Normalização do bullying como ritual de interação entre jovens nas escolas públicas - Bonfim, Rodrigo Oliveira (2022)
This study aimed to analyze the micro-interactionist relationships of public school students whose main normalized ritual is bullying. In addition to understanding how symbols that are considered important for the maintenance of the domination ritual are produced. Also analyze the importance of the performance of these actors and actresses involved in this symbolic interaction whose main characteristic is the domination of one individual over the other. As methods of measuring data, quantitative and qualitative tools were used so that there was a greater coverage of the social phenomenon, since this is a dynamic social construction and requires greater proximity to the actors and actresses present in the micro situation. As a quantitative tool, the questionnaire was used, as the main guide of the students' perception of the phenomenon studied, since their perspective becomes complete for the work, since it served to understand the depth of knowledge of the bullying of these students and these students. For the qualitative tool, two kinds of methods were used: the focus group and the face-to-face interview. Through the formation of focus groups, a greater scope was allowed regarding the symbols found in the ritual, what are the perspectives of the victims and the spectators regarding the micro situation in which they were inserted. The face-to-face interview was of great value because it brought a more intimate contribution thanks to the secrecy in which the researcher and the interviewee were. During these several interesting aspects were collected, among these some testimonies in which the interviewees showed themselves in the role of aggressor or aggressor, an important ingredient for understanding the situation and the individuals involved. This dissertation brought a proposal linked to micro interactionist sociology, whose focus is directed to micro interactions and their rituals. The proposal established by this academic work takes place in the field in which symbols are socially constructed in the form of networks of interaction rituals, seeking to perceive bullying within the school space, its actors and actresses, its symbols contained in these rituals that become the main tools. of domination in the face of the micro situational environment, it was noticed that the main form of domination within the bullying rituals. And as a result it was noticed that the main form of domination within the bullying rituals is given by symbols transmitted by other networks of interaction rituals.